The Oligarchisation of India's Democracy: Evidence from Andhra Pradesh and Odisha - Berenschot, Ward; Bagchi, Sarthak; Vignesh, Karthik KR (Economic and Political Weekly, 2024)
The intensifying fusion of political and economic power in India is discussed. Employing data on the wealth and background of politicians, it is shown that over the last 20 years, India's politicians have not only become much wealthier but also more commo
Keywords: India's Democracy; Parliamentary Elections; Political and Economic Power; Oligarchisation